Advances in New Zealand's tephrochronostratigraphy using marine drill sites: the neogene - Pank, Katharina; Kutterolf, Steffen; Hopkins, J. L.; Wang, K.-L.; Lee, H.-Y.; Schmitt, Axel Karl (Geochemistry, geophysics, geosystems, 2023)
Three volcanic arcs have been the source of New Zealand's volcanic activity since the Neogene: Northland arc, Coromandel Volcanic Zone (CVZ) and Taupō Volcanic Zone (TVZ). The eruption chronology for the Quaternary, sourced by the TVZ, is well studied and established, whereas the volcanic evolution of the precursor arc systems, like the CVZ (central activity c. 18 to 2 Ma), is poorly known due to limited accessibility to, or identification of, onshore volcanic deposits and their sources. Here, we investigate the marine tephra record of the Neogene, mostly sourced by the CVZ, of cores from IODP Exp. 375 (Sites U1520 and U1526), ODP Leg 181 (Sites 1123, 1124 and 1125), IODP Leg 329 (Site U1371) and DSDP Leg 90 (Site 594) offshore of New Zealand. In total, we identify 306 primary tephra layers in the marine sediments. Multi-approach age models (e.g. biostratigraphy, zircon ages) are used in combination with geochemical fingerprinting (major and trace element compositions) and the stratigraphic context of each marine tephra layer to establish 168 tie-lines between marine tephra layers from different holes and sites. Following this approach, we identify 208 explosive volcanic events in the Neogene between c. 17.5 and 2.6 Ma. This is the first comprehensive study of New Zealand's Neogene explosive volcanism established from tephrochronostratigraphic studies, which reveals continuous volcanic activity between c. 12 and 2.6 Ma with an abrupt compositional change at c. 4.5 Ma, potentially associated with the transition from CVZ to TVZ.